2020
DOI: 10.1155/2020/6030581
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy Using HMME for Port-Wine Stains: Clinical Effectiveness and Sonographic Appearance

Abstract: This study aims at exploring the clinical efficacy and sonographic changes of photodynamic therapy (PDT) using Hematoporphyrin Monomethyl Ether (HMME) for the treatment of port-wine stains (PWS). Forty-five patients with PWS were recruited between March 2017 and June 2018 from the Department of Dermatology of The Third Affiliated Hospital of Soochow University. Five cases were of the pink type, thirty-nine cases were of the purple-red type, and one case was of the thickened type. All patients received three tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
(28 reference statements)
0
24
1
Order By: Relevance
“…Previous studies have shown that regardless of the lesion site, size, or type, the total effective rate of HMME-PDT treatment of PWSs in different age groups can be as high as 97.78% and 99.75% [17,18]. of patients showed an excellent efficacy (cured) after two HMME-PDT treatments, 41.46% showed good efficacy, and showed alleviation (fair) where most of the patients were of the pink type [9].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that regardless of the lesion site, size, or type, the total effective rate of HMME-PDT treatment of PWSs in different age groups can be as high as 97.78% and 99.75% [17,18]. of patients showed an excellent efficacy (cured) after two HMME-PDT treatments, 41.46% showed good efficacy, and showed alleviation (fair) where most of the patients were of the pink type [9].…”
Section: Discussionmentioning
confidence: 99%
“…Natural polymer materials include chitosan, alginate, and collagen, which have the advantages of good biocompatibility, no immunogenicity, and non-toxic degradation products ( Table 1 ). However, the mechanical properties of natural high molecular polymers are poor, and the degradation rate is too fast, so they are rarely used in the preparation of a single scaffold [ 24 , 25 , 26 ]. Artificial synthetic materials include polylactic acid, polylactic acid, and polycaprolactone (PCL).…”
Section: Bioceramic 3d Printing Overviewmentioning
confidence: 99%
“…Uses and applications of bioactive components cover a wide range of sectors, especially nutraceuticals [5][6][7]. In vitro [8] and in vivo [9] studies assessing the beneficial effects of nutraceutical models were presented, in particular studies on the nutritional supplements in animals [10][11][12]. At the same time, particular researches on botanicals have been described by [13][14][15] concentrating on the importance of those sources of vegetable origin (see Figure 1).…”
Section: Nutraceuticalsmentioning
confidence: 99%